Tailoring Circular Dichroism in an Isomeric Manner: Complete Control of Amplitude and Phase for High‐Quality Hologram and Beam Forming. Issue 3 (6th December 2021) - Li, Yongfeng; Pang, Yongqiang; Wang, Jiafu; Zheng, Qiqi; Zhang, Jieqiu; Zhang, Jingjing; Jing, Yao; Zheng, Lin; Feng, Maochang; Wang, He; Qu, Shaobo; Cui, Tiejun
Abstract: Nowadays, the research of metasurfaces has been developed from single‐dimensional toward multi‐dimensional manipulation of electromagnetic (EM) waves, which greatly boosts the practical application of metasurfaces in both microwave and optics regimes. Currently, the demand for new methods to implement effective manipulation of EM waves in multiple dimensions is ever being increased yet it is still a challenging task. Here, a metasurface‐based paradigm is proposed for tailoring both amplitude and phase by isomeric manner in a dichroism level, which reveals a flexible capability of manipulating EM waves within all isotropic, anisotropic and chiral characteristics. Circular dichroism (CD) meta‐atoms are implemented via loading lumped resistors into planar chiral resonators. The cross‐polarization reflection amplitude of the circularly polarized wave is tailored precisely and continuously from 0 to 1 using the diastereomers of CD meta‐atoms, while the phase is independently manipulated by the rotamer counterparts based on Pancharatnam‐Berry (PB) phase. By controlling both amplitude and phase profiles of the metasurfaces with subwavelength spatial resolution, high‐quality complex amplitude hologram and far‐field beam forming are demonstrated. Encouragingly, this approach for achieving simultaneous control of amplitude and phase makes a milestone on multi‐dimensional metasurfaces which may find applications in integrated planar EM functional systems. Abstract : A metasurface‐based paradigm of tailoring both amplitude and phase by isomeric manner in a dichroism level is proposed, which reveals a flexible capability to manipulate electromagnetic waves within all isotropic, anisotropic, and chiral characteristics. Based on this method, rectangular‐shaped beam forming metasurfaces and complex amplitude hologram metasurfaces are validated.